Incidência do staphylococcus aureus na produção do queijo de coalho artesanal e qualidade de novas formulações - Medeiros, Jovilma Maria Soares de (2020)
In view of the need for food with sanitary and nutritional quality, the objective was to characterize Staphylococcus aureus present in the production of artisanal “coalho” cheese, as well as the use of natural products (herbs and inulin) in the preparation of this product. For this purpose, colonies of S. aureus present in milk, equipment and utensils used in the manufacture, stages of preparation and the final product of two producing establishments were isolated, totaling 52 samples. Colon phenotypic identification, search for genes encoding enterotoxins, antibiotic resistance and typing by agr typing were performed, in addition to antibiotic sensitivity testing. Two artisanal “coalho” cheeses were made. In one production, the substitution of sodium chloride for herbs in the proportions of 30%, 22.2% and 12.5% was used. Semi-skimmed and whole milk was also used with the addition of 8% inulin in the production of the second product. In the samples of the two cheeses manufactured, microbial growth, chemical composition and physical parameters were analyzed during 10 days of cold storage and sensory analysis was performed. In the production process of “coalho” cheese, high contamination (50%) by S. aureus was observed, as well as the presence of a gene producing sea enterotoxin (19%) and a mecA gene (45.7%). The genes of the agr groups were present in the cheese production process with a higher prevalence of agr III (12.7%). Regarding antibiotic resistance, multiple resistance to penicillin, oxacillin, erythromycin and clindamycin was observed in 79% of the isolates. In herbal formulations it was possible to reduce the counts of coagulase positive staphylococci (5.64 log CFU / g) until the 5th day of storage, as well as the sodium content and improve the acceptance of the cheese with the addition of 12.5% of herbs. In relation to inulin, it didn’t interfere with microbial growth and maintained the sensory acceptance equivalent to “coalho” cheese without inulin. In establishments where the production of “coalho” cheese was analyzed, strains of S. aureus with enterotoxygenic potential were found, demonstrating the need for manufacturing with better hygiene conditions. In addition, the addition of herbs can be an alternative to improve microbiological quality, which combined with the use of inulin improves the nutritional quality of “coalho” cheese.